Barriers and challenges for primary care service in the COVID-19 pandemic - Dela Erjalia; Rizma Adlia Syakurah (Intelektual Pustaka Media Utama, 2021)
The COVID-19 pandemic is such a barrier for health systems around the world including Indonesia. Primary care is the first-line in controlling the pandemic at the community level, but there are many barriers and challenges faced by doctors during the service that are not fully recognized. This aimed to distinguish barriers and challenges in health centers and/clinics amid the COVID-19 widespread. This was qualitative study with a phenomenological approach. As much 44 health centers/clinical specialists interviewed in October 2020. Then, the data categorization method/coding and content analysis used. There were three themes related to the barriers and challenges confronted by specialists in health centers/clinics, specifically barriers and challenges based on service management, environment, and individuals. The barriers and challenges confronted are related to changes within the consultation flow, a diminished number of patient visits, limited supplies of personal protective equipment (PPE), patient states of mind and behavior within the confront of a pandemic, and progressively heavier burdens and duties for doctors. It is necessary to provide specific, valid, and right-on-target knowledge in improving community behavior in efforts to prevent COVID-19 infection and the government's important role to be more concerned about the future of health workers.